Concerns over confidentiality may deter adolescents from consulting their doctors. A qualitative exploration. Issue 3 (28th February 2006) - Carlisle, J; Shickle, D; Cork, M; McDonagh, A
Abstract : Objectives: Young people who are concerned that consultations may not remain confidential are reluctant to consult their doctors, especially about sensitive issues. This study sought to identify issues and concerns of adolescents, and their parents, in relation to confidentiality and teenagers' personal health information. Setting: Recruitment was conducted in paediatric dermatology and general surgery outpatient clinics, and on general surgery paediatric wards. Interviews were conducted in subjects' own homes. Methods: Semistructured interviews were used for this exploratory qualitative study. Interviews were carried out with 11 young women and nine young men aged 14–17. Parents of 18 of the young people were interviewed separately. Transcripts of tape recorded interviews provided the basis for a framework analysis. Results: Young women were more concerned than young men, and older teenagers more concerned than younger teenagers, about people other than their general practitioner (GP) having access to their health information. Young people with little experience of the healthcare system were less happy than those with greater knowledge of the National Health Service (NHS) for non-medical staff to access their health information. As they grow older, adolescents become increasingly concerned that their health information should remain confidential. Conclusion: Young people's willingness to be open in consultations could be enhanced by doctors taking time to explain to them that their discussion is completely confidential. Alternatively, if for any reason confidentiality cannot be assured, doctors should explain why.